Treefrogs adjust their acoustic signals in response to harmonics structure of intruder calls. (25th March 2021) - Foratto, Roseli Maria; Llusia, Diego; Toledo, Luís Felipe; Forti, Lucas Rodriguez
Abstract: Spectral properties of animal acoustic signals may help individuals to assess the characteristics of rivals and to adjust their competitive strategies in territorial disputes. Thus, we hypothesized that the distribution of energy across frequency bands in anuran calls determines behavioral responses in male–male competition. Using playback experiments, we investigated the relevance of the harmonic calls in the acoustic communication of the treefrog Dendropsophus minutus . We exposed territorial males to three synthetic acoustic stimuli composed of aggressive notes: 1) standard call (all harmonics and peak frequency corresponding to the second band); 2) inverted-energy call (all harmonics and peak frequency corresponding to the first band); and 3) concentrated-energy call (all energy contained in the second harmonic). Males responded aggressively to all stimuli, mainly by increasing the rate and duration of their aggressive notes. However, when exposed to stimuli with different harmonic configurations, males changed the harmonic structure of their own calls, emitting more A- and B-notes with peak power in the fundamental frequency, particularly when exposed to the concentrated-energy call. Our results suggest that male frogs may use the harmonic structure of calls to assess opponents and modulate territorial and aggressive behavior, triggering complex acoustic adjustments. This study contributes to our knowledge about the functions of acoustic traits in amphibian social interactions, and particularly of the presence of harmonics that has received less attention compared to other acoustic properties in the study of animal acoustic communication. Abstract : Harmonics are synchronously emitted frequencies, where the highest sound is an integer multiple of the lower frequency. The significance of harmonic signals in animal communication is not well known. We exposed territorial treefrogs to aggressive signals of the same species, varying the harmonic structure. Males exhibited similar behavior in response to all signals, but they changed the harmonic structure of the calls depending on the stimuli. Our results suggest that energy distribution across harmonics do not perform a strong role in male-male competition, but may trigger call adjustments depending on the intruder call.